2014
DOI: 10.1152/jn.00275.2014
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor patterns in cerebellar ataxia

Abstract: Several studies have demonstrated how cerebellar ataxia (CA) affects gait, resulting in deficits in multijoint coordination and stability. Nevertheless, how lesions of cerebellum influence the locomotor muscle pattern generation is still unclear. To better understand the effects of CA on locomotor output, here we investigated the idiosyncratic features of the spatiotemporal structure of leg muscle activity and impairments in the biomechanics of CA gait. To this end, we recorded the electromyographic (EMG) acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 62 publications
5
99
0
Order By: Relevance
“…Thus, the impaired characteristics of the inter-segmental coordination (the shape of the gait loop and its orientation, Figure 3B) and changes in activation timings (Figures 5C, 7C) may be indicative of a possible alteration of the oscillatory commands in children with CP. Finally, the immature developmental state of the cerebellum (Vasudevan et al, 2011) may also contribute, since wider EMG bursts have been previously reported in cerebellar patients (Hallett et al, 1975; Martino et al, 2014). Whatever the exact mechanism for wider bursts of muscle activity, it represents the characteristic feature of spinal motoneuronal output in CP (Figures 4–7).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, the impaired characteristics of the inter-segmental coordination (the shape of the gait loop and its orientation, Figure 3B) and changes in activation timings (Figures 5C, 7C) may be indicative of a possible alteration of the oscillatory commands in children with CP. Finally, the immature developmental state of the cerebellum (Vasudevan et al, 2011) may also contribute, since wider EMG bursts have been previously reported in cerebellar patients (Hallett et al, 1975; Martino et al, 2014). Whatever the exact mechanism for wider bursts of muscle activity, it represents the characteristic feature of spinal motoneuronal output in CP (Figures 4–7).…”
Section: Discussionmentioning
confidence: 96%
“…The CI was assessed between the thigh (mean activity of quadriceps RF-VL-VM vs. hamstring BF-ST) and calf (mean activity of triceps MG-LG-SOL vs. TA) antagonistic muscle groups using the following formula (Rudolph et al, 2000; Martino et al, 2014): leftCI=falsefalsej=1200[(EMGH(j)+EMGL(j)/2)]×(EMGL(j)/EMGH(j))200 where EMG H and EMG L represent the highest and the lowest activity between the antagonist muscle pairs (EMG activity for each muscle was normalized to its maximum value). In order to have a global measure of the co-activity level, the CI was then averaged over the entire gait cycle ( j = 1:200).…”
Section: Methodsmentioning
confidence: 99%
“…When these parameters are analyzed as continuous variables, only minimal differences, mainly involving the ankle joints, are revealed between patients and controls [123]. Abnormal intra-limb joint coupling during walking, in terms of both joint movements and interaction torques, has been reported in several studies [122, 123, 131133]. Particularly, increased temporal variability of intra-limb coordination has been found to be related with dynamic balance and irregular foot trajectories in ataxic gait [132].…”
Section: Gait/posture In Cerebellar Disorders (Carlo Casali and Mariamentioning
confidence: 99%
“…In two recent studies investigating the spatial and temporal profiles of EMG activity in individual muscles [133] as well as in paired antagonist muscles [138], a common pattern has been shown. Specifically, a marked widening of the EMG peaks and a high level of ankle and knee joint muscles co-contraction were observed during all four gait sub-phases.…”
Section: Gait/posture In Cerebellar Disorders (Carlo Casali and Mariamentioning
confidence: 99%
“…The cerebellum plays a critical role in the coordination of locomotion (Armstrong, 1988; Arshavsky et al, 1986; Shik and Orlovsky, 1976), and damage to the cerebellar vermis severely impairs the control of limbs and posture in animal models and in human patients (Dow and Moruzzi, 1958; Martino et al, 2014; Morton and Bastian, 2004). Furthermore, mouse mutant lines with cell-type-specific abnormalities in the cerebellar cortex exhibit locomotor deficits in speed, accuracy, consistency, and multi-joint coordination (Vinueza Veloz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%